Husband’s Support is a Main Factor Associated with Contraceptive Practices - Darrell Fernando; Rachmat Dediat (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To determine factors associated with contraceptive practices in Palabuhanratu, West Java. Method: We conducted a cross-sectional study at the Obstetrics and Gynecologic ward of Local General Hospital of Palabuhanratu District, between March and June 2012. Data was collected using directed interview method by investigators and midwives, using non-validated questionnaires. Statistical analysis was performed using SPSS 20.0, utilizing Chi-Square test for nominal data and Kruskal-Wallis test for numerical data. Result: We obtained 71 samples. The only factors which are significant were age group of 20-35 years old (OR=3.5, 95%CI=1.1-11.1, p=0.025) and husband’s support (OR=14.67, 95%CI=1.52-141.18, p=0.012). The most recognized contraceptive methods familiar to our respondents were injection (94.4%) and pills (93.0%), and the most useful source of information on contraception was medical personnel (73.2%). Conclusion: Husband’s support is a main factor associated with contraceptive practice. The choice of contraceptive method should be adjusted according to the ability and desire of patients to prevent failures in family planning. Keywords: associated factors, contraception, husband’s support